Android Phishing Analysis with the Reverse Engineering Method Using MT Manager - Ika Mei Lina; Gilang Ryan Fernandes (Politeknik Piksi Ganesha Indonesia, 2024)
People spend a lot of time with gadgets every day, and it cannot be denied that gadgets can facilitate people's activities in various fields. However, even though gadgets are very helpful, there are digital crimes that we must be aware of. One case that has received a lot of attention is the method of providing online invitations and package delivery receipts in the form of malware spread via the WhatsApp chat application. This has caused many losses, such as losing money in banking and also confidential data being accessed by criminals. The aim of this research is so that the public can anticipate this crime. Researchers use the Reverse Engineering method to find out the process, patterns, design, and how a program works in detail. The results obtained from this research are that there are many hacker attacks in the form of malware applications. This malware application will run when the victim downloads, installs, and grants access permission to the application. So people should always be alert and careful when using gadgets in everyday life.